PERSEPSI DAN MOTIVASI MAHASISWA TERHADAP STUDI DI UTM BANGKALAN - Elita Yuvika Wulandari; Nurul Imamah (Universitas Trunojoyo Madura, 2018)
ABSTRACTThe aim of this study was to obtain data on the perception and motivation of students towards the study of lecturer’s general subjects (MKU), to answer the question, whether there is an effect of student perception and motivation towards the study of lecturer’s general subjects (MKU) on learning outcomes. We tested 20 students drawn from the population of students participating in MKU, using multistage random sampling technique. The results of data analysis concludes that there is significant effect of student perception and motivation towards the study of lecturer’s general subject (MKU) on learning outcomes, or in other words, the better and stronger the perception and motivation of students are, the better the students’s absorbtion. Through MKU, expected the third mission can be achieved, the competence of MKU’s lecturers need to be improved, permanently.